Employee Engagement, Komitmen Organisasi, dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi (Suatu Kajian Studi Literatur Manajemen Sumberdaya Manusia) - Catur Wahyuningsih; Maswanto; Suhendar Sulaeman; Abdul Jamil (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Previous research and relevant research are very useful for research or literature review of scientific work, whether studying the influence between variables or other factors that influence a variable itself. This article discusses a literature review of factors that influence employee performance, namely job satisfaction which is used as an intervening variable, employee engagement, organizational commitment, and organizational culture. This article was written to design hypotheses that influence variables so that they can be used in subsequent studies. The results of this study are: 1) Employee engagement has a positive and crucial influence on job satisfaction; 2) organizational commitment has a positive or crucial impact on job satisfaction; 3) organizational culture has a positive or crucial impact on job satisfaction; 4) Employee engagement has a positive and crucial influence on employee performance; 5) Organizational culture has a positive and crucial influence on employee performance; 6) Job satisfaction has a positive and crucial influence on employee performance. 7) Job satisfaction can mediate employee engagement which influences employee performance. 8) Job satisfaction can mediate organizational culture which influences employee performance.